2018
DOI: 10.3390/electronics7110296
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Coupled Resonance WPT: Review of Compensation Topologies, Resonator Structures with Misalignment, and EMI Diagnostics

Abstract: Magnetically coupled resonance wireless power transfer systems (MCR WPT) have been developed in recent years. There are several key benefits of such systems, including dispensing with power cords, being able to charge multiple devices simultaneously, and having a wide power range. Hence, WPT systems have been used to supply the power for many applications, such as electric vehicles (EVs), implantable medical devices (IMDs), consumer electronics, etc. The literature has reported numerous topologies, many struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 180 publications
0
113
0
Order By: Relevance
“…Under the proposed control condition based on (14), the voltage and the current distribution are analyzed as follows:…”
Section: Currents and Voltages Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…Under the proposed control condition based on (14), the voltage and the current distribution are analyzed as follows:…”
Section: Currents and Voltages Distributionmentioning
confidence: 99%
“…(b) The voltages U i2 at the receiver coils generally remain unchanged despite the variation of β i1 . It is because based on the constant output voltage condition the output voltage U o remains unchanged, and the β i2 has to remain unchanged based on (14) to provide high efficiency. Therefore, according to (3), the voltages U i2 at the receiver coils generally remain unchanged.…”
Section: Currents and Voltages Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [8], the authors propose a simple method for the analysis of the resonance frequency of a planar spiral coil to evaluate the lumped parameters of the coils. Using the technology of electromagnetic resonant couplings WPT [9], the authors addressed the fact that the output power can reach 100 W. Ref. [10] showed that magnetic resonant coupling WPT normally works in megahertz and its efficiency is improved with increasing frequency.…”
Section: Introductionmentioning
confidence: 99%